Facial recognition as a force for good. (March 2019) - Watts, Rob
Abstract : Facial recognition has become one of the most widely discussed technology solutions in recent years. Advocates such as myself point to its ability to make us all safer, to offer added convenience to users and to underpin operational efficiencies. Meanwhile critics tend to fall into one of two camps. They either claim it doesn't work, or conversely that it is an invasion of privacy and therefore a threat to society. Some of the concerns about how the technology is to be deployed are valid. However, history has almost always shown that those who seek to stand in the way of technological advancement find themselves on the wrong side of the debate.